2021
DOI: 10.3390/nu13020553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Restriction and Water Replenishment on the Content of Body Water with Bioelectrical Impedance among Young Adults in Baoding, China: A Randomized Controlled Trial (RCT)

Abstract: Insufficient water intake may affect body composition. The purpose of this research was to explore the effects of water restriction and replenishment on body composition and to evaluate the optimum amount of water that improves body composition. A total of 76 young adults aged 18–23 years old (40 males and 36 females) in Baoding, China, were recruited in this randomized controlled trial, with a 100% completion rate. After fasting overnight for 12 h, at 8:00 a.m. of day 2, a baseline test, including anthropomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Furthermore, women were more sensitive to water supplementation than men, which was consistent with other studies, with more aspects of body composition changed in women than that of men ( 31 ). A study conducted among 56 male wrestlers has reported that, after drinking a carbohydrate–electrolyte solution, the ECW significantly decreased incrementally from the pre-dehydration test to rehydration test; even after 2 hours of rehydration, the ECW did not return to the baseline level ( 53 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, women were more sensitive to water supplementation than men, which was consistent with other studies, with more aspects of body composition changed in women than that of men ( 31 ). A study conducted among 56 male wrestlers has reported that, after drinking a carbohydrate–electrolyte solution, the ECW significantly decreased incrementally from the pre-dehydration test to rehydration test; even after 2 hours of rehydration, the ECW did not return to the baseline level ( 53 ).…”
Section: Discussionsupporting
confidence: 91%
“…One study investigating the effects of different volumes of water on TBW has revealed that, after 500 mL of water supplementation, an increase in TBW by 0.21 kg was found in men, but not in women ( 67 ). Similarly, another study has shown that participants who consumed 1,000 mL of water had higher TBW than their counterparts who drank nothing ( 31 ). The intervals used for measuring the changes in the TBW, as well as the types of fluids supplied to the participants, could explain the differences in the abovementioned studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although there are multiple techniques for the measurement of body fluid compartments, bioimpedance spectroscopy (BIS) remains a reliable, costeffective technology that identifies body composition by sending electrical waves and estimating resistance values from very high to very low resistance numbers [5]. In addition, BIS allows measuring water compartments separately (total body water (TBW), ECW, and ICW) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Determining the body liquid volume has been useful in some diseases such as renal disorders and heart failure (7,8). Moreover, the ratio between extracellular and intracellular fluid has been proposed as an index of health status (9). Nevertheless, TBW has not been previously evaluated in patients with PSS who suffer from impaired production of tears and saliva, both of them as previously mentioned constituted by a high percentage of water.…”
Section: Introductionmentioning
confidence: 99%